Mental health law in Pakistan - Amina Tareen; Khalida Ijaz Tareen (BJPsych International, 2016)
Continued efforts to produce appropriate mental health legislation in Pakistan led to the Mental Health Ordinance of 2001. However, with the 18th amendment to the constitution and devolution of health responsibilities to the provincial governments, it became the task of the provinces to pass appropriate mental health legislation through their respective assemblies. Currently the mental health legislative picture is fragmented and unsatisfactory. Only the provinces of Sindh and Punjab have a mental health act in place and there is an urgent need for similar legislative frameworks in other provinces to protect the rights of those with mental illness.